DÖNME KUANTUM SAYISI İZDÜŞÜMLERİNİN REAKSİYON KİNETİKLERİNE ETKİSİNİN ARAŞTIRILMASI - ASLAN, EMİNE (Fırat Üniveristesi, 2009)
Martinazzo ve çalışma arkadaşları tarafından hesaplanan ab initio potansiyel enerji yüzeyi üzerinde Li+H2+ reaksiyonunun dinamik ve kinetikleri, kuantum mekaniksel dalga paketi metoduna dayanan akı analizi metodu yaklaşımı kullanılarak hesaplandı. Eşik enerjisinden 1.0 eV çarpışma enerjisine kadar toplam açısal momentum kuantum sayısı J=0 değeri için reaksiyon ihtimaliyetleri elde edildi. Reaksiyon ihtimaliyetleri J=0' dan belli J değerleri için J=90' a kadar Helissel ayrışma yaklaşımı kullanılarak hesaplandı. J>0 için integral tesir kesitleri ve reaksiyon hız sabitleri, Helissel ayrışma yaklaşımı ile elde edilen reaksiyon ihtimaliyetlerinin kullanıldığı interpolasyona dayalı J-kayma yaklaşımı ile hesaplandı. Helissel kuantum sayılarının (K) reaksiyon dinamik ve kinetikleri üzerine etkileri detaylı olarak araştırıldı. Hesaplanan reaksiyon hız sabitlerinin bir Arhenius davranışı sergilediği gözlendi. Elde edilen kuantum mekaniksel sonuçların kuasiklasik sonuçlar ile uyumlu olduğu gözlendi

The dynamics and kinetics of the Li+H2+ reaction have been studied by means of a quantum mechanical wave packet method with flux operator approach on the ab initio potential energy surface of Martinazzo et al. Total initial state-selected reaction probabilities for the Li+H2+ reaction have been calculated for total angular momentum J=0 at collision energies from threshold up to 1 eV. Wave packet reaction probabilities at selected values of the total angular momentum up to J=90 were obtained using the Helicity Decoupling Method. Integral cross sections and rate constants were calculated from the wave packet reaction probabilities by means of a refined J-shifting method (based on interpolation) in combination with the Helicity Decoupling Method for J>0. The effect of the helicity quantum numbers (K) on the reactivity was investigated. It was found that the calculated rate constants as a function of temperature show an Arhenius type behavior. The quantum mechanical results were founded to be in overall good agreement with the corresponding quasiclasical trajectory data.
The investigation of the effect of helicity quantum numbers on the reaction kinetics
Keywords: Fizik ve Fizik Mühendisliği